UNIVERSALITY OF ISLAMIC WORK ETHICS ON BANKING EMPLOYEES IN INDONESIA AND ITS IMPACT ON ORGANIZATIONAL COMMITMENT - Sri Mulyono; Yuliana Yuliana; Wahyu Wiguna; Ahmad Mukhlis (Yayasan Education and Social Center, 2023)
There is a scarcity of credible Islamic human resources who are not only professionals in banking operations but also understand, animate, and implement Islamic teachings in a comprehensive way. The purpose of this research is to show whether the Islamic work ethic is universal and to analyze whether the Islamic work ethic influences organizational commitment. The research method uses descriptive analysis and simple linear regression using SPSS. The results of his research are that the Islamic work ethics of bank employees show a high value scale (good) and that Islamic work ethics have a significantly positive effect on the organizational commitment of conventional banks and Islamic banks